Method for in-situ preparation of conformal ion device

The preparation of ionic conductive elastomer coatings through the synergistic action of hydrazide and lithium salts solves the problem of preparing flexible electronic devices on complex surfaces, achieves efficient and accurate in-situ preparation, improves the performance and stability of the device, and is suitable for a variety of purposes Base material, and is erasable and recyclable.

CN119264804AActive Publication Date: 2025-01-07ZHEJIANG UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411824693.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-07
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently and accurately prepare flexible ion conductive elastomer coatings in situ on complex, dynamic surfaces, limiting the application and stability of flexible electronic devices on irregular surfaces.

Method used

Through the synergistic action of hydrazide and lithium salt, an ionic conductive elastomer coating with adjusting tensile strength and tensile modulus was prepared. The coating process was used to form an ionic conductive elastomer coating on the target substrate, realizing the complex surface Efficient and accurate preparation.

Benefits of technology

It realizes efficient and precise preparation on complex surfaces, improves the performance and stability of the device, has excellent mechanical properties, conductive properties and adhesion, is suitable for different substrate materials, and is erasable and recyclable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264804A_ABST
    Figure CN119264804A_ABST
Patent Text Reader

Abstract

The invention discloses a method for in-situ preparation of a conformal ion device, which comprises the following steps: dehydrating 10-15 parts by weight of polyester glycol to obtain a dehydrated product; reacting the dehydration product with 0.22-0.33 part by weight of isofluorodiketone diisocyanate in the presence of a solvent and an organic tin catalyst; adding 0.9-1 part by weight of a hydrazide compound and 40-80 parts by weight of DMF (Dimethyl Formamide) into a reaction product, and continuously reacting to generate a u-TPU / DMF solution; adding a lithium salt into the solution, and removing redundant DMF to concentrate the solution to obtain an ionic conductive elastomer coating ICEP; and curing the ICEP on the surface of a target substrate by a coating method to obtain an ionic conductive elastomer coating ICEC for in-situ preparation of an ionic device. According to the method for in-situ preparation of the conformal ion device provided by the invention, efficient and accurate preparation of the soft ion electronic device on a complex surface can be realized without depending on an external transfer process, so that the performance and the stability of the device are effectively improved; the problem that a flexible ion electronic device is difficult to integrate on a complex three-dimensional surface in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ion-conductive elastomers and in-situ preparation of conformal ion devices, and in particular to a method for in-situ preparation of conformal ion devices. Background Art

[0002] With the rapid development of flexible electronics, more and more electronic devices need to be able to adapt to complex surface shapes and dynamically changing environments. Traditional rigid electronic devices often cannot achieve good performance and stability under these conditions. Therefore, how to manufacture flexible electronic devices that meet the requirements on irregular, curved or dynamic surfaces has become an important challenge in current technology. In recent years, ion-conducting elastomers have become a research hotspot in the field of flexible electronics due to their excellent conductivity, flexibility and elasticity. This material has high ionic conductivity and good mechanical flexibility, and can provide stable electrical properties on irregular surfaces. However, the application of existing ion-conducting elastomer materials is mostly limited to flat or relatively regular surfaces, and in-situ preparation and integration on complex and dynamic surfaces still face certain difficulties.

[0003] Current technologies mainly rely on prefabricated ion-conductive elastomer films, which are applied to the target surface by bonding or other means, making it difficult to achieve efficient and precise in-situ manufacturing on complex surfaces. In addition, existing methods usually require complex equipment and processes, which cannot meet the needs of fast and low-cost production, and also limit their promotion and popularization in practical applications. For example, a Chinese patent with publication number CN118440368A discloses an all-solid-state ion conductive elastomer film and a preparation method and application thereof, comprising: removing water from thermoplastic polyurethane particles in an oven, and then completely dissolving them in an anhydrous organic solvent to obtain a thermoplastic polyurethane solution; respectively dissolving lithium salt, polyethylene glycol, diisocyanate, and catalyst in the thermoplastic polyurethane solution, and removing bubbles by ultrasound to obtain a mixed solution; pouring the mixed solution into a mold, ventilating it for natural volatilization, and transferring it to an oven for complete polymerization after there is no organic reagent odor to obtain an all-solid-state ion conductive elastomer film; the collaborative design of the all-solid-state ion conductive elastomer and its preparation method proposed in the invention enrich the preparation strategy of the conductive elastic system and provide new ideas for the preparation of more all-solid-state ion conductive elastomer materials with excellent mechanical toughness and good conductivity. A Chinese patent with publication number CN117924647A discloses a preparation method and application of polyurethane and polyurethane-based ion conductive elastomer, wherein the main raw materials for preparing the polyurethane-based ion conductive elastomer are as follows: 20 to 100 parts of lithium bistrifluoromethanesulfonyl imide and 100 parts of polyurethane; a preparation method and application of polyurethane and polyurethane-based ion conductive elastomer, wherein the main raw materials for preparing the polyurethane are as follows: 20 to 30 parts of polytetramethylene ether glycol, 40 to 60 parts of 3,3-4,4'-dicyclohexylmethane diisocyanate, 2 to 10 parts of 4,4-bismaleimide diphenylmethane, 1 to 3 parts of a catalyst, 5 to 20 parts of a chain extender, and 5 to 20 parts of 2,5-furan dimethanol. The main raw materials for preparing the polyurethane-based ion conductive elastomer are as follows: 20-100 parts of lithium bis(trifluoromethanesulfonyl)imide and 100 parts of polyurethane in weight parts; the preparation process is as follows: lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) is dissolved in an anhydrous organic solvent and then mixed with polyurethane for 5 hours to obtain a mixed solution, and then the mixed solution is placed on a hot plate at 80-90°C to evaporate the solvent to obtain the polyurethane-based ion conductive elastomer.

[0004] Therefore, there is an urgent need for a technology that can directly prepare ion-conductive elastomer coatings in situ on complex surfaces and realize the integration of soft ionic electronic devices. Summary of the invention

[0005] The purpose of the present invention is to provide a method for in-situ preparation of conformal ionic devices. Through the method of the present invention, efficient and precise preparation of soft ionic electronic devices on complex surfaces can be achieved without relying on external transfer processes, thereby effectively improving the performance and stability of the device and solving the problem of difficulty in integrating flexible ionic electronic devices on complex three-dimensional surfaces in the prior art.

[0006] The present invention adopts the following technical solutions to achieve the above purpose: The present invention provides a method for in-situ preparation of a conformal ion device, comprising the following steps: (1) dehydrating 10 to 15 parts by weight of polyester diol to obtain a dehydrated product; reacting the dehydrated product with 0.22 to 0.33 parts by weight of isofluorodione diisocyanate in the presence of a solvent and an organic tin catalyst; (2) adding 0.9 to 1 parts by weight of a hydrazide compound and 40 to 80 parts by weight of N,N-methylformamide (DMF) to the reaction product of step (1) to continue the reaction to generate a u-TPU / DMF solution; wherein the hydrazide compound is represented by formula (I), formula (II) or formula (III): ; (3) adding lithium salt to the solution obtained in step (2), and removing excess DMF to concentrate the solution to obtain an ion conductive elastomer coating ICEP; (4) The ICEP obtained in step (3) is post-cured on the surface of the target substrate by coating to obtain an ion conductive elastomer coating ICEC to prepare an ionic device in situ.

[0007] The ion conductive elastomer coating prepared by hydrazide and lithium salt forms an ion conductive elastomer coating after film formation, and the synergistic effect of lithium salt and urea bond groups in TPU enables the tensile strength and tensile modulus of the coating to be adjusted within a wide range of 50Mpa-3Mpa and 8.34Mpa-2.31Mpa to meet the needs of different target substrates.

[0008] In step (1), the polyester diol is preferably terminal hydroxyl poly (ε-caprolactone) with a molecular weight of 1000-3000; this is conducive to increasing the viscosity of the polyurethane, thereby preparing an ion conductive elastomer coating with excellent performance; the reaction temperature is 60°C-90°C, preferably 75°C-80°C; the reaction time is 2-5h, preferably 3h; this is conducive to improving the mechanical properties of the ion conductive elastomer coating.

[0009] In step (1), the dehydrated product is prepared by the following steps: 10-15 parts by weight of polyester diol and 0.03-0.06 parts by weight of catalyst are mixed, and dehydrated under reduced pressure at 120° C. to 140° C. for 1-3 hours to obtain a dehydrated product. The catalyst is an organic tin catalyst, preferably dibutyltin dilaurate. This is conducive to improving the degree of reaction.

[0010] The isophorone diisocyanate in step (1) can be 2.2 to 3.3 parts by weight, preferably 2.8 to 3.0 parts by weight, which is beneficial to improving the tensile properties of the ion conductive elastomer coating.

[0011] The solvent in step (1) is selected from N,N-dimethylformamide, N,N-dimethylacetamide, acetone, tetrahydrofuran, preferably N,N-dimethylformamide. The amount used can be 0-10 ml, preferably 5 ml.

[0012] In step (2), the hydrazide compound is selected from isophthaloyl hydrazide, o-phthaloyl hydrazide, terephthaloyl hydrazide, preferably isophthaloyl hydrazide. The amount of the hydrazide compound added may be 0.9 to 1 parts by weight, preferably 0.95 to 0.97 parts by weight.

[0013] In step (2), the reaction temperature is 20°C to 50°C, preferably 40°C to 45°C, and the reaction time is 8 to 24 hours, preferably 12 to 15 hours. This is conducive to improving the degree of reaction and increasing the mechanical properties of the ion conductive elastomer coating.

[0014] The solvent in step (2) is selected from N,N-dimethylformamide and N,N-dimethylacetamide, preferably N,N-dimethylformamide.

[0015] In step (3), the mass ratio of lithium salt to u-TPU is 1:1.2~1:5.7, and the solid content of the ion conductive elastomer coating is 30wt%~50wt%.

[0016] The lithium salt added in step (3) is preferably LiTFSI. The amount added can be 15-45wt% (the content of the lithium salt is the mass percentage of the lithium salt in the u-TPU). The mechanical properties and conductive properties of the final film-forming ion conductive elastomer coating can be adjusted according to the amount of LiTFSI added. The conductive properties can be adjusted between 1.08×10 -3 S / m~53.23×10 -3 The specific amount of LiTFSI added can be determined according to the requirements of different substrates.

[0017] In step (3), excess DMF is removed by a rotary evaporator to concentrate the solution, thereby obtaining an ion conductive elastomer coating having a viscosity of 0.026 to 10.29 Pa·s. The viscosity of the coating will affect the coating effect of the conductive coating on the substrate. The appropriate viscosity of the coating can be determined according to substrates of different shapes and requirements.

[0018] The process for preparing the coating on the target substrate in step (4) includes: brushing, dipping, spin coating, casting or printing.

[0019] The appropriate molding process and coating viscosity can be selected according to the different shapes and materials of the substrates to ensure that the ion conductive elastomer coating is evenly covered on surfaces of different complex shapes. The target substrate is selected from glass, metal, plastic, rubber or polyacrylic elastomer.

[0020] In step (4), the film formation of the ion conductive elastomer coating is mainly to volatilize the DMF solvent in the solution, thereby preparing the ion conductive elastomer coating. The main method includes: high temperature baking and room temperature placement. Room temperature placement is preferred because it can protect the base material.

[0021] The substrate surface in step (4) can be a stretchable surface, such as a polyacrylate elastomer or a rubber material; a non-expandable surface, such as a hemisphere, a Möbius ring, etc.; a rough surface, such as a brick, an uneven surface of an object, a robot arm, etc.

[0022] According to the preparation method of the ionic coating of the present invention, due to the multi-scale design inside the ionic conductive elastomer coating, its mechanical properties can be adjusted by changing the LiTFSI content to achieve adaptation to different substrate materials. Different contents of LiTFSI can make the ionic conductive elastomer coating have different mechanical properties: low content of LiTFSI makes the ionic conductive elastomer coating have high modulus and strength, suitable for application to hard substrates to withstand mechanical loads; while high content of LiTFSI gives the ionic conductive elastomer coating higher flexibility, suitable for use on soft substrates, and will not affect the deformation of the substrate.

[0023] When the target substrate is glass, metal or plastic, the content of lithium salt in the ion conductive elastomer coating is 15~30wt%; when the target substrate is rubber or polyacrylate elastomer, the content of lithium salt in the ion conductive elastomer coating is 30wt%~45%; wherein the content of lithium salt is the mass percentage of lithium salt in u-TPU.

[0024] The flexible conformal ionic device in step (4) includes: a strain sensor, a triboelectric generator, and a capacitive ionic skin. The dielectric layer of the triboelectric generator and the capacitive ionic skin is prepared by brushing the precursor liquid of Ecoflex. The appropriate coating viscosity, coating conductivity, and coating mechanical properties can be selected according to different needs and scenarios to prepare a conformal ionic device that is more closely attached to the substrate.

[0025] Compared with the prior art, the present invention has the following excellent effects: In the method for in-situ preparation of conformal ionic devices provided by the present invention, the obtained ion-conductive elastomer coating with a high LiTFSI content exhibits low hysteresis and small residual strain in a loading / unloading cycle with a maximum strain of 500%, effectively reducing viscoelasticity and improving elastic recovery performance; In the method for in-situ preparation of conformal ionic devices provided by the present invention, the thickness of the ion conductive elastomer coating can be controlled by adjusting the coating viscosity and the number of brushing times, and can effectively conduct electricity after applying voltage; in addition, the ion conductive elastomer coating has high transparency, and the light transmittance can meet the requirements of optoelectronic applications; Sudan III red dye can be added to increase the contrast; In the method for in-situ preparation of conformal ionic devices provided by the present invention, the ion-conductive elastomer coating exhibits excellent adhesion on different substrates. For impermeable substrates (such as glass and metal), the ion-conductive elastomer coating is in close contact with the surface and exhibits high adhesion energy; on permeable substrates (such as polyacrylate), the coating can penetrate into the polyacrylate and form topological entanglement with the substrate network, which greatly improves the adhesion energy. This strong adhesion method ensures the stability and adaptability of the ion-conductive elastomer coating on complex substrates; In the method for in-situ preparation of conformal ionic devices provided by the present invention, the ion conductive elastomer coating has unique erasability and recyclability. The coating can be completely dissolved by DMF solvent, so that the coating can be easily erased. The coating obtained after dissolution can be recycled and reused after removing the solvent by a rotary evaporator. In the method for in-situ preparation of conformal ionic devices provided by the present invention, an ion conductive elastomer coating is prepared by directly coating an ion conductive elastomer coating on a target substrate, and the coating can be used to prepare a conformal flexible strain sensor and a moisture generator; a conformal friction generator is prepared by coating an ion conductive elastomer coating-Ecoflex coating on a substrate in the order of ion conductive elastomer coating-Ecoflex coating; a conformal capacitive pressure sensor is prepared by coating an ion conductive elastomer coating-Ecoflex coating-ion conductive elastomer coating on a substrate in the order of ion conductive elastomer coating-Ecoflex coating-ion conductive elastomer coating; In summary, the present invention realizes efficient and simple in-situ manufacturing of conformal soft ionic electronic devices by using ion conductive elastomer coating and synergistic control technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The mechanical properties of the ion conductive elastomer coating at different lithium salt contents prepared in Example 1; the synergistic effect of urea bonds and LiTFSI enables the mechanical properties of the coating to be adjusted over a wide range to meet the needs of different substrates; Figure 2 A schematic diagram of forming an ion-conductive elastomer coating by coating the ion-conductive elastomer coating prepared in Example 1 on different target substrates; Figure 3 is the adhesion energy of ion-conducting elastomer coatings to different target substrates; Figure 4 A flexible conformal ion-conducting elastomer coating prepared on the balloon surface; Figure 5 is the hysteresis rate and residual strain of the ion conductive elastomer coating at different lithium salt contents; Figure 6 Cyclic stretching of ion-conducting elastomeric coatings at high lithium salt content; Figure 7 The transparency test results of the ion conductive elastomer coating are shown; Figure 8 for the re-brushable effect of the ion-conductive elastomer coating; Fig. 9 The conductive effect of the ion-conductive elastomer coating; Fig.10 The comparison between the conformal device prepared by brushing and the device prepared by mapping in Example 2; Fig.11 The comparison between the conformal device prepared by brushing and the device prepared by mapping on the uneven surface in Example 2; Fig.12 For the printing process using ICEP; Fig.13 A photograph of the conformal resistor sensor fabricated in situ by brushing on the uneven inner surface of the pneumatic robot arm in Example 2; Fig.14 is the measured resistance of the conformal resistance sensor during arm bending of the pneumatic manipulator in Example 2; Fig.15 Schematic diagram of a triboelectric nanogenerator (TENG) formed on a glass rod by dip coating in Example 2; Fig.16 The short-circuit current and open-circuit voltage generated by the conformal TENG in Example 2. DETAILED DESCRIPTION

[0027] In the following Examples and Comparative Examples, "parts" refer to parts by weight unless otherwise stated.

[0028] The raw materials used in the embodiments and comparative examples are introduced below: Isophorone diisocyanate (IPDI), N,N-dimethylformamide (DMF), isophthalic acid hydrazide (ID), 1,4-butanediol (BDO), and bis(trifluoromethanesulfonyl)imide lithium salt (LiTFSI) were purchased from Shanghai MacLean. Polycaprolactone diol (PCL, Mn = 2000) was purchased from Tianjin Heowns Opde Technology Co., Ltd. Dibutyltin dilaurate (DBTDL) was purchased from TCI Shanghai. All chemicals were used as received without further purification.

[0029] Example 1

[0030] The method for preparing the ion conductive elastomer coating provided in this embodiment comprises the following steps: 10 parts of hydroxy-terminated poly(ε-caprolactone) (PCL, Mn=2000 g / mol) were added to a three-necked flask, heated to 140°C, dehydrated under reduced pressure for 3h, then cooled to 80°C, 3.0 parts of isofluorinated dione diisocyanate (IPDI), 0.06 parts of dibutyltin dilaurate (DBTDL) and 5ml of DMF were added to continue the reaction for 2h, and after the reaction, the temperature was cooled to 40°C, 0.97 parts of isophthalic acid hydrazide (ID) was added as a chain extender, and 60 parts of DMF were added again to continue the reaction for 10h. u-TPU / DMF solution was obtained. A specific content (15 wt%, 30 wt%, 45 wt% relative to u-TPU) of LiTFSI was added to the solution to prepare an ion conductive solution with specific mechanical properties and conductive properties, and then the excess DMF was removed by a rotary evaporator to obtain ion conductive elastomer coatings (ICEPs) with different viscosities and solid contents for different manufacturing processes.

[0031] Mechanical properties of ion-conductive elastomer coatings at different lithium salt contents Figure 1 As shown: The synergistic effect of urea bonds and LiTFSI allows the mechanical properties of the coating to be adjusted over a wide range to meet the needs of different substrates.

[0032] Ion-conducting elastomeric coatings (ICECs) are prepared on complex surfaces using a variety of fabrication processes, such as Figure 2 As shown: In the brush coating process, ICEP with a solid content of 50 wt% is applied to a substrate with complex curved surfaces, such as spherical and saddle-shaped surfaces. The coating is applied using a brush 1 to evenly distribute the coating ICEP2 on the surface of the target 3. The ICEC formed after the solvent evaporates and solidifies at room temperature can highly match the surface morphology, light up the LED bulb under applied voltage, and show good conductivity and surface consistency. The coating thickness of a single brush coating is controlled by controlling the solid content of the coating, which is approximately between 0.07 and 0.33 mm. Multiple brushing can produce thicker coatings.

[0033] like Fig. 9 As shown, the coating can light up the LED bulb when electricity is applied, and the surface has excellent conductivity.

[0034] The adhesion of the coating to different substrates was measured by a 90° peel test. Figure 3 As shown. For impermeable substrates, excellent adhesion can be achieved due to the good adhesion between the coating and the substrate. For permeable substrates, the coating can generate topological entanglement with the substrate, thereby greatly improving the adhesion performance.

[0035] Choose a coating with a suitable formulation according to the properties of the substrate. For example, for balloons, a coating with a low modulus should be selected (when the lithium salt content is high), because during the balloon expansion process, the coating with a lower modulus will not have a significant impact on the substrate, that is, the coating will not affect the deformation of the balloon. Figure 4 shown.

[0036] In the dip coating process, ICEP with different solid contents is dip coated on PVC and glass rod 4. By controlling the viscosity and solid content of the coating, ICEC with different thicknesses between 26.42 μm and 182.53 μm can be formed, and excellent conductivity can be exhibited.

[0037] In the spin coating process, ICEP is coated on the substrate using a spin coater 5 and a dropper 6 and evenly distributed at a rotation speed of 300 r / min. The thickness can range from 7.68 μm to 418.1 μm according to different viscosities and rotation speeds, which is suitable for flexible electronic applications.

[0038] In the casting process, ICEP is directly poured into the template 7 for curing, so as to form an ICEC film with a specific shape and thickness, meeting the requirements of precise manufacturing.

[0039] After ICEC is prepared by casting method, the hysteresis rate and residual strain of ICEC under different formulations can be tested by cyclic tensile test. Figure 5 and Figure 6As shown, ICEC with high LiTFSI content has lower hysteresis and residual strain, which benefits from the synergistic effect of urea bond and LiTFSI. The coating at this time has very low hysteresis, which is conducive to the preparation of devices on flexible and stretchable substrates.

[0040] After ICEC was prepared by casting method, the transparency of ICEC was measured by UV spectrophotometer. Figure 7 As shown, all samples exhibited high transparency (>80%).

[0041] In the printing process, ICEP can also be integrated into a high-precision microelectronic printer 8 to print conductive circuits on rigid nylon boards to achieve the production of microelectronic circuits with complex structures, such as Fig.12 As shown (the printer can print ion-conducting circuits on rough surfaces).

[0042] The coating can be wiped off with a solvent (DMF), and the resulting DMF solution can be concentrated to re-prepare high-viscosity ICEP, thereby achieving the recovery and reuse of ICEC. Figure 8 shown.

[0043] Comparative Example 1 The only difference from Example 1 is that 1,4-butanediol (BDO) is used to replace isophthalic acid hydrazide. The process parameters are shown in Table 1.

[0044] Table 1 Process parameters of Example 1 and Comparative Example 1 .

[0045] The following describes the preparation of flexible conformable electrodes in embodiments and comparative examples.

[0046] Example 2

[0047] The method of preparing a multilayer conformal soft ion electronic device on a complex surface by using ICEP provided in Example 2 comprises the following steps: Preparation steps for flexible conformal electrodes on complex surfaces: The ICEP with a solid content of 50 wt% (LiTFSI content is 45 wt% relative to u-TPU) prepared in Example 1 was brushed on the non-developable surface (saddle shape, spherical shape) and the uneven surface, and ICEC was obtained after curing. ICEC can be well attached to the surface without any gaps and wrinkles, such as Fig.10 and Fig.11 As shown: The coating prepared by brushing has very good adhesion, while the mapping method will have wrinkles and cracks when pasted on non-developable surfaces and uneven surfaces.

[0048] Steps for preparing conformal strain sensors on the surface of pneumatic robot arms: By applying ICEP to the wavy inner side of a pneumatic manipulator to form an ICEC layer, a conformal resistive strain sensor was fabricated in situ and connected to a test device (digital multimeter) via metal wires to monitor the motion of the manipulator. Fig.13 As shown. Due to the excellent compliance and elastic behavior of ICEC, the resistance of the coating changes instantaneously when the robotic arm is bent and extended. The greater the degree of arm bending, the greater the change in coating resistance, which can be used to monitor the degree of bending of the robotic arm, such as Fig.14 shown.

[0049] Steps for preparing a double-layer triboelectric nanogenerator (TENG) by dip coating on a cylindrical surface: The conformal triboelectric nanogenerator (TENG) was prepared by sequentially dipping a plastic rod into ICEP and uncured Ecoflex preconditioner, as Fig.15 The resulting double-layer TENG consists of an inner ICEC layer and an outer Ecoflex dielectric layer that conformally wraps the plastic rod, as shown in Fig.15 As shown. When the plastic stick coated with TENG is tapped onto the metal plate, TENG can stably output a voltage of 2 V and a current of 15 μA, as shown Fig.16 As shown, it exhibits excellent conformality and stable electrical signal output.

[0050] Comparative Example 2 Conformable flexible electrodes were prepared on complex surfaces by replacing ICEP with conventional stretchable adhesive tape (VHB).

[0051] 1. Experimental example The ion conductive elastomer coatings prepared in Example 1 and Comparative Example 1 were punched out to produce 12 mm×2 mm×0.3 mm tensile dumbbell-shaped specimens, which were respectively named Example Specimen 1 and Comparative Example 1, for testing.

[0052] 2. Tensile test The following method was used to conduct tensile tests on the properties of the samples of the embodiments and comparative examples: an electronic universal material testing machine (Instron 3343, sensor 50 N) was used to conduct tensile tests on the samples at a tensile speed of 100 m / min.

[0053] The test results are shown in Table 2: Table 2 Tensile properties of the samples of Example 1 and Comparative Example 1 ; Butanediol cannot provide enough hydrogen bonds, so that after adding a large amount of lithium salt, the material cannot be formed. This reflects the importance of the urea bond designed by the present invention to enhance the synergistic effect between u-TPU and lithium salt.

[0054] 3. Fit performance test The ion conductive elastomer coatings prepared on the complex surface in Example 2 and Comparative Example 2 were observed to see whether there were gaps or wrinkles between the substrate and the coating. The test results are shown in Table 3: Table 3 The adhesion performance of the ion conductive elastomer coating prepared on the complex surface in Example 2 and Comparative Example 2 ; This example demonstrates the versatility and applicability of ICEP to fabricate multilayer conformal electronic devices on complex three-dimensional surfaces. These ICEP-based devices have low hysteresis, high elasticity, and excellent consistency, and are suitable for humidity power generation, strain detection, and pressure sensing, overcoming the limitations of traditional ex situ fabrication and providing new application pathways for soft ion electronic devices on complex surfaces.

Claims

1. A method for in-situ preparation of conformal ion devices, characterized in that: The method comprises: (1) dehydrating 10 to 15 parts by weight of polyester diol to obtain a dehydrated product; reacting the dehydrated product with 0.22 to 0.33 parts by weight of isofluorodione diisocyanate in the presence of a solvent and an organic tin catalyst; (2) Add 0.9 to 1 parts by weight of a hydrazide compound and 40 to 80 parts by weight of N,N-methylformamide DMF to the reaction product of step (1) and continue the reaction to generate a u-TPU / DMF solution; wherein the hydrazide compound is represented by formula (I), formula (II) or formula (III): ; (3) adding lithium salt to the solution obtained in step (2), and removing excess DMF to concentrate the solution to obtain an ion conductive elastomer coating ICEP; (4) The ICEP obtained in step (3) is post-cured on the surface of the target substrate by coating to obtain an ion conductive elastomer coating ICEC to prepare an ionic device in situ.

2. The method for in-situ preparation of conformal ion devices according to claim 1, characterized in that: In step (1), 10-15 parts by weight of polyester diol and 0.03-0.06 parts by weight of a catalyst are mixed, and dehydrated under reduced pressure at 120° C.-140° C. for 1-3 hours to obtain a dehydrated product; wherein the catalyst is an organic tin catalyst.

3. The method for in-situ preparation of conformal ion devices according to claim 1, characterized in that: In step (2), the reaction temperature is 20°C to 50°C.

4. The method for in-situ preparation of conformal ion devices according to claim 1, characterized in that: In step (3), the mass ratio of the lithium salt to the u-TPU is 1:1.2-1:5.7, and the solid content of the ion conductive elastomer coating is 30wt%-50wt%.

5. The method for in-situ preparation of conformal ion devices according to claim 1, characterized in that: In step (3), the solution is concentrated by removing excess DMF using a rotary evaporator to obtain an ion conductive elastomer coating with a viscosity of 0.026 to 10.29 Pa·s.

6. The method for in-situ preparation of conformal ion devices according to claim 1, characterized in that: In step (4), the target substrate has a complex three-dimensional surface, and the coating method is brushing, dipping, spin coating, pouring or printing.

7. The method for in-situ preparation of conformal ion devices according to claim 1, characterized in that: In step (4), the target substrate has a complex three-dimensional surface, and the target substrate is selected from glass, metal, plastic, rubber or polyacrylic elastomer.

8. The method for in-situ preparation of conformal ion devices according to claim 7, characterized in that: When the target substrate is glass, metal or plastic, the content of lithium salt in the ion conductive elastomer coating is 15~30wt%; when the target substrate is rubber or polyacrylate elastomer, the content of lithium salt in the ion conductive elastomer coating is 30wt%~45%; wherein the content of lithium salt is the mass percentage of lithium salt in u-TPU.

9. The method for in-situ preparation of conformal ion devices according to claim 1, characterized in that: In step (4), the ionic device is a strain sensor, a friction nanogenerator or a capacitive ionic skin.

10. The method for in-situ preparation of conformal ion devices according to claim 9, characterized in that: ICEP is coated on the wavy inner side of a pneumatic manipulator and cured to form an ICEC layer to prepare a conformal strain sensor; or a plastic rod is sequentially immersed in ICEP and an uncured Ecoflex preprocessor to prepare a conformal triboelectric nanogenerator.

Citation Information

Patent Citations

  • Preparation method and application of polyurethane and polyurethane-based ionic conductive elastomer

    CN117924647A

  • All-solid-state ionic conductive elastomer film as well as preparation method and application thereof

    CN118440368A

  • Dynamic supramolecular ion conductive elastomer and preparation method thereof

    CN114230757A

  • Lignin-based polyurethane elastomer with high strength and high thermal stability as well as preparation method and application of lignin-based polyurethane elastomer

    CN116874739A

  • Ultra-high-performance transparent self-repairing polyurethane-urea film capable of being recycled repeatedly and preparation method of ultra-high-performance transparent self-repairing polyurethane-urea film

    CN117624538A